Hubungan Pola Asuh Orang Tua Yang Demokratis Dengan Perilaku Sosial Siswa Kelas IX SMP N 2 Harian Kabupaten Samosir Tahun 2023 - Immanuel Valentino Hutapea; Haposan Silalahi; Robinhot Sihombing (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to determine the relationship between democratic parenting patterns and the social behavior of Class IX students at SMP N 2 Harian 2023. The method used in this research is quantitative descriptive statistics. The population is all 41 class IX students of SMP N 2 Harian in 2023 and were designated as research data collection. Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive relationship between Parenting Patterns and Social Behavior of Class IX Students of SMP N 2 Harian 2023, which is proven by carrying out: 1) testing the positive relationship, the value obtained is rxy = 0,482 > rtabel(=0,05,n=41) = 0,308, thus it is known that there is a positive relationship between variable X and variable Y. 2) Test the hypothesis using the t test to obtain tcount > ttabel namely 3,431 > 2,021. Thus Ha is accepted and H0 is rejected..